Relevansi Pendidikan Bisnis dalam Meningkatkan Minat Berwirausaha Mahasiswa Fakultas Ekonomi UNIMED di Tengah Ketidakpastian Ekonomi: The Relevance of Business Education in Increasing Entrepreneurial Interest of UNIMED Faculty of Economics Students Amidst Economic Uncertainty - Roza Thohiri; Delpina Sinambela; Maria Teresia Manalu; Janli Aman Saragih; Tri Bunga Arthaty; Lita Nurmeli Parhusip; Eleseria Oktavia Aritonang; Helen Natalia Kembaren (ITScience (Information Technology and Science), 2026)
Economic uncertainty encourages students to be prepared to face workplace challenges and to contribute to entrepreneurial activities. However, some students still feel hesitant to start a business despite having received a business education. This study aims to evaluate the relationship between business education and increased entrepreneurial interest among students in the Faculty of Economics at the State University of Medan (UNIMED). This study employs a quantitative, correlational survey method. Data collection was conducted using a Likert-scale questionnaire distributed to students of the Faculty of Economics at the State University of Medan (UNIMED). Data analysis was carried out using descriptive statistics, correlation analysis, and simple linear regression. The results showed that business education has a positive and significant effect on students' entrepreneurial interest in the Faculty of Economics at the State University of Medan. Simple linear regression analysis yielded a coefficient of 0.447 and a significance value of 0.000 (<0.05), indicating that improving the quality of business education is associated with increased student entrepreneurial interest. Validity tests showed that all statement items had calculated r values greater than the table r, so the instrument was declared valid. The reliability test yielded Cronbach's alphas of 0.842 for the business education variable and 0.856 for entrepreneurial interest, indicating that the research instrument is reliable. The coefficient of determination (R²) of 0.564 indicates that business education explains 56.4% of the variation in students' entrepreneurial interest, with 43.6% attributable to other factors outside the research model. These results indicate that business education makes a fairly strong contribution to shaping entrepreneurial interest. However, it is not the sole factor, as psychological and environmental factors still influence it.